A checklist of the Amphibians and Reptiles of Costa Rica: Additions and nomenclatural revisions - Savage, Jay M.; Bolaños, Federico (Zootaxa, 2009)
A list of amphibians and reptiles of Costa Rica is actualized. A total of 425 species (190 amphibians and 235 reptiles) are recognized.